Chemical composition, antioxidant and antibacterial properties of Pteranthus dichotomus from Algerian Sahara. Issue 6 (18th March 2016) - Allaoua, Zina; Benkhaled, Mohammed; Dibi, Ammar; Long, Christophe; Aberkane, Mohammed Cherif; Bouzidi, Soumia; Kassah-Laouar, Ahmed; Haba, Hamada
Abstract : The phytochemical study of ethyl acetate and n -butanol extracts of Pteranthus dichotomus Forssk. led to the isolation and identification of 11 compounds, including three glycolipids1 –3, one lignan4, three flavonoids5 –7 and four phytosterols8 –11 . Structures of the isolated compounds have been elucidated by analysis of 1D and 2D NMR data, and mass spectrometry EI-MS and ESI-MS and by comparison with literature data. Furthermore, the ethyl acetate and n -butanol extracts were examined for their antioxidant and antibacterial activities. The results showed that both extracts ( PD AC and PD BU) had a moderate antioxidant activity (IC50 = 375.514 μg/mL and 691.333 μg/mL) respectively. Abstract :